Seismic Response Of A Sandy Stratum With A Silt Layer Under Strong Ground Motions - Bakhtiar Cahyandi Ridla; Huei -Tsyr Chen; M. Ruslin Anwar (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2012)
The presence of silt layer with small permeability may exist in the liquefiable sandy ground and it can produce the water film beneath silt layer with high pore water pressure under earthquakes. From the geotechnical point of view, the water film can cause instability of ground especially for slope ground. The objectives of this study is to gain a more understanding the effect of possible crack inside the silt layer at certain time on the seismic responses of ground of liquefiable sand stratum with a silt layer through numerical simulations. A nonlinear 3D effective stress finite element program was used in this study. A total of 4 models were constructed. Two strong earthquakes with different characteristic were used in this study. Settlement on the surface and excessive pore water pressure were presented for all models. The result showed that possible crack in the silt layer can lead to the larger settlement due to the faster dissipation of EPWP beneath the silt layer and the breakage of silt layer can lead to the sudden decrease in EPWP in the soil beneath the silt layer and sudden increase in EPWP in the soil above the silt layer. Sometimes the upward movement of pore water may cause the soil to liquefy, which will not occur without the breakage of silt layer. The crack in the silt layer leads to the faster dissipation of EPWP below the silt layer; such faster dissipation progresses from the location beneath the silt layer to the bottom of the soil stratum.